Don't be my valentine - Lexau, Joan M.; Hoff, Syd, 1912- (New York, N.Y. : Harper & Row, 1985)
Sam's mean valentine for Amy Lou goes astray at school and almost ruins the day for him and his friends.
School Library Journal
Basal Reading Program
1.6
K-3
Keywords: Valentines -- Fiction; Valentine's Day -- Fiction; Friendship -- Fiction; Schools -- Fiction; Valentines -- Fiction; Valentine's Day -- Fiction; Friendship -- Fiction